Effect of Piperine on Diameter of Graafian Follicles of Adult Female Albino Rats - Saqib Mansoor, Asma Zulfiqar, Asma Siddique, Uzma Ali, Kanwal Sharif, Muhammad Suhail, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Piperine is an alkaloid present in black pepper. It causes increase in diameter of Graafian follicles when given to adult female albino rats thus leading to decreased fertility. Aim: To assess the harmful effects of piperine on ovaries of adult female albino rats on diameter of Graafian follicles. Study design: Experimental Study. Place and duration of study: Anatomy Department, Shaikh Zayed PGMI, Lahore from 1st August 2013 to 31st January 2014. Methodology: Thirty female rats were randomly separated into three equal groups A, B and C, each having 10 animals. Group A was control and did not receive any medication except for normal saline at a dose of 10ml/kg body weight/day by orogastric tube for 30 days. Group B and C received piperine suspended in saline by orogastric tube, at a dose of5mg/kg/day and 10 mg/kg/day respectively for 30 days. After 30 days of experiment, the rats of all three groups were euthanized and ovaries were removed by dissection and then fixed in 10% formalin. With rotary microtome, 4-5μm sections were prepared and stained with hematoxylin and eosin solutions. Results: The Graafian follicle in ovaries of rats in group B showed increased diameter as compared to control group A. The diameter of Graafian follicles of group C was greater than of group B. In both groups comparison was made, the p-value was less than 0.001. Conclusion: Piperine administration in female adult albino rats showed significant increase in size of Graafian follicle which is likely to produce polycystic ovarian syndrome (PCOS) and in this way hamper fertility in females during child bearing age. Keywords: Piperine, Albino rat, Ovaries, Fertility, Polycystic ovarian syndrome (PCOS)